2018
DOI: 10.1002/14651858.cd013021
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel node biopsy for diagnosis of lymph node involvement in endometrial cancer

Abstract: This is a protocol for a Cochrane Review (Diagnostic test accuracy). The objectives are as follows:To assess the diagnostic accuracy of sentinel lymph node biopsy in the identification of pelvic lymph node involvement in women with apparent early stage endometrial cancer. Sentinel node biopsy for diagnosis of lymph node involvement in endometrial cancer (Protocol)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 28 publications
2
17
1
1
Order By: Relevance
“…These and other studies demonstrated that SLN injection and biopsy improved the detection rates of positive lymph nodes principally through the detection of low-volume metastatic disease with ultrastaging [12]. It appears that SLN detection rates do not differ significantly between the different tracers and sites of injection with most authors favoring ICG and cervical injections [13]. However, the prognostic significance and therapeutic implications of micrometastases, and more importantly ITC, remains unclear [14].…”
Section: Endometrial Cancermentioning
confidence: 87%
“…These and other studies demonstrated that SLN injection and biopsy improved the detection rates of positive lymph nodes principally through the detection of low-volume metastatic disease with ultrastaging [12]. It appears that SLN detection rates do not differ significantly between the different tracers and sites of injection with most authors favoring ICG and cervical injections [13]. However, the prognostic significance and therapeutic implications of micrometastases, and more importantly ITC, remains unclear [14].…”
Section: Endometrial Cancermentioning
confidence: 87%
“…Even though ICG SLN mapping showed no false negative, full lymphadenectomy should be performed to assess the diagnostic accuracy of the sentinel lymph node biopsy. The risk of recurrence or residual disease following surgery would be increased if full lymphadenectomy was not performed after the sentinel lymph node biopsy (10). Because ultrastaging of the sentinel lymph node is a limitation of micrometastasis in the pathological report, diagnostic accuracy remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple tracers have been used for SLN mapping in EC, including blue dye, technetium-99 (Tc-99), and indocyanine green (ICG). The combination of Tc-99 and blue dye has an average detection rate of 86.3% (80.7–91.9%) [ 41 ]. However, this tracer requires collaboration with a nuclear medicine unit and preoperative imaging, which increases the cost and requires a painful preoperative injection for patients [ 42 ].…”
Section: Sentinel Lymph Node Mapping In Endometrial Cancermentioning
confidence: 99%